Neonatal- maternal separation primes zymogenic cells in the rat gastric mucosa through glucocorticoid receptor activity - Daniela Ogias (Nature Portfolio, 2018)
Abstract Neonatal- Maternal Separation (NMS) deprives mammals from breastfeeding and maternal care, influencing growth during suckling- weaning transition. In the gastric mucosa, Mist1 (encoded by Bhlha15 gene) and moesin organize the secretory apparatus for pepsinogen C in zymogenic cells. Our current hypothesis was that NMS would change corticosterone activity through receptors (GR), which would modify molecules involved in zymogenic cell differentiation in rats. We found that NMS increased corticosterone levels from 18 days onwards, as GR decreased in the gastric mucosa. However, as nuclear GR was detected, we investigated receptor binding to responsive elements (GRE) and observed an augment in NMS groups. Next, we demonstrated that NMS increased zymogenic population (18 and and 30 days), and targeted Mist1 and moesin. Finally, we searched for evolutionarily conserved sequences that contained GRE in genes involved in pepsinogen C secretion, and found that the genomic regions of Bhlha15 and PgC contained sites highly likely to be responsive to glucocorticoids. We suggest that NMS triggers GR- GRE to enhance the expression and to prime genes that organize cellular architecture in zymogenic population for PgC function. As pepsinogen C- pepsin is essential for digestion, disturbance of parenting through NMS might alter functions of gastric mucosa in a permanent manner.